Sites of Liberation or Sites of Despair?: The Challenges and Possibilities of Democratic Education in an Urban Public School in New York City. (December 2015) - Hantzopoulos, Maria
Abstract : This article considers the possibilities of critical democratic education through the lived experiences of students at an urban U.S. public school. I show how students shape their own educational trajectories amid larger meta‐narratives about schooling to illuminate the complexities and paradoxes of democratic schools. I argue that democratic schools are neither sites of transformation nor sites of despair, but rather sites where agency is negotiated, contested, and remade, often in unexpected, unassuming, and contradictory ways.